Secondary Metabolites with Anti-Inflammatory Activity from Laurencia majuscula Collected in the Red Sea - Mohamed A. Tammam; Maria G. Daskalaki; Nikolaos Tsoureas; Ourania Kolliniati; Aldoushy Mahdy; Sotirios C. Kampranis; Christos Tsatsanis; Vassilios Roussis; Efstathia Ioannou (Marine Drugs, 2023)
The chemical investigation of the organic extract of the red alga Laurencia majuscula collected from Hurghada reef in the Red Sea resulted in the isolation of five C15 acetogenins, including four tricyclic ones of the maneonene type (1–4) and a 5-membered one (5), 15 sesquiterpenes, including seven lauranes (6–12), one cuparane (13), one seco-laurane (14), one snyderane (15), two chamigranes (16, 17), two rearranged chamigranes (18, 19) and one aristolane (20), as well as a tricyclic diterpene (21) and a chlorinated fatty acid derivative (22). Among them, compounds 1–3, 5, 7, 8, 10, 11 and 14 are new natural products. The structures and the relative configurations of the isolated natural products have been established based on extensive analysis of their NMR and MS data, while the absolute configuration of maneonenes F (1) and G (2) was determined on the basis of single-crystal X-ray diffraction analysis. The anti-inflammatory activity of compounds 1, 2, 4–8, 10, 12–16, 18 and 20–22 was evaluated by measuring suppression of nitric oxide (NO) release in TLR4-activated RAW 264.7 macrophages in culture. All compounds, except 6, exhibited significant anti-inflammatory activity. Among them, metabolites 1, 4 and 18 did not exhibit any cytostatic activity at the tested concentrations. The most prominent anti-inflammatory activity, accompanied by absence of cytostatic activity at the same concentration, was exerted by compounds 5 and 18, with IC50 values of 3.69 μM and 3.55 μΜ, respectively.